Voluntary disclosure of investment information at Malaysian companies website / Azrul Abdullah... [et al.] - Abdullah, Azrul; Mohd Isa, Rosiatimah; Mat Isa, Norshamshina; Alias, Ahmad Zoolhelmi (Universiti Teknologi MARA, Perlis, 2011)
This paper examined the voluntary investment information disclosed by Malaysian listed companies via their websites. A total of 100 companies listed on the Mainboard Bursa Malaysia were selected based on their market capitalization in attempting to explain the disclosure practices. Investment informations disclosure via the websites were analyzed across industry based on the score in the designated disclosure form. This study also identified the format of presentation for investment information in terms of multimedia usage. Finding of the study highlighted that the investment information disclosure and usage of the multimedia were still unsatisfactory.